The Role of Corporate Governance on Stakeholder Pressure and Integrated Reporting - Putri Nurmala; Akhmad Sigit Adiwibowo (Jurnal ASET (Akuntansi Riset), 2023)
This research examines the effect of stakeholder pressure on integrated reporting and the role of corporate governance as a moderating variable on the effect of stakeholder pressure on integrated reporting. Integrated reporting has been a re-search focus for a decade, but its effect on stakeholder pres-sure and corporate governance needs to be studied more. This study used 150 sample data from LQ45 companies listed on the Indonesian Stock Exchange between 2017 and 2021, and hypotheses were tested using panel regression. Accor-ding to the study's findings, the pressure from stakeholders does not affect integrated reporting. According to the study's findings, corporate governance cannot moderate the effects of stakeholders' pressure on integrated reporting. It shows that management's motivation to implement integrated rep-orting is only sometimes to maintain its reputation among shareholders. This study contributes to academic research on management's motivation to disclose integrated repor-ting, particularly in Indonesia. It may also explain why earlier studies contradicted when businesses had high liquidity in integrated reporting. The novelty of this research is that usi-ng samples of LQ45 companies with high stock liquidity is the main focus for investors to invest their funds in the Indon-esian capital market, making these research findings reflect stakeholders' pressure of integrated reporting practices.